The High Commissioner on National Minorities as a Normative Actor - Jennifer Jackson-Preece (Journal on Ethnopolitics and Minority Issues in Europe, 2013)
The High Commissioner on National Minorities' (HCNM) role as a normative actor is significant both for understanding the success of this specific instrument as well as the crucial importance of norms in diffusing and ultimately overcoming minority/majority tensions more generally. Security, like politics, is a fundamentally normative activity. Within this context, actors engage in a political process intended to secure a particular normative outcome. In the HCNM's case, that outcome is security for minorities and majorities understood as a plural democracy in which diversity is recognized and respected.